Pituitary hormone deficiencies in prolactinomas: prevalence, predictors, and functional recovery - Prinzi, Antonio; Fava, Ginevra; Bacchi, Ignazio; Spitali, Federica; Galvano, Antonio; Arnaldi, Giorgio; Frasca, Francesco; Guarnotta, Valentina; Malandrino, Pasqualino (Frontiers in Endocrinology, 2025)
IntroductionTo evaluate the prevalence of pituitary hormone deficiencies in patients with prolactinomas, identify clinical and radiological predictors of non-gonadal hypopituitarism at diagnosis, and evaluate the potential for pituitary function recovery over long-term follow-up.MethodsWe conducted a retrospective multicenter study including 145 patients with prolactinomas diagnosed between 2000 and 2024 at two tertiary centers. All anterior pituitary axes were evaluated at diagnosis and during follow-up.ResultsAt diagnosis, 54 of 145 patients (37.2%) had at least one pituitary hormone deficiency. Hypogonadism was the most common deficit (34.5%), followed by non-gonadal hypopituitarism in 14.5%, including secondary adrenal insufficiency: 8.3%, central hypothyroidism: 7.6%, growth hormone deficiency (GHD): 6.9%. Macroadenomas were significantly more prevalent than microadenomas (25.8% vs. 2.7%, p<0.001). Tumor size was the only independent predictor of non-gonadal hypopituitarism at diagnosis (OR: 1.1, 95%CI: 1.03–1.20; p=0.007). ROC analysis identified 17 mm as the optimal cut-off to predict non-gonadal pituitary hormone deficiencies at diagnosis (sensitivity 84%, specificity 77%, AUC = 0.836). During follow-up (median 70 months), 66.7% of patients recovered at least one pituitary axis, with higher recovery in microadenomas (100% vs. 63.0%, p=0.038). Tumor size remained the strongest predictor of recovery (OR: 0.56, 95%CI: 0.34–0.94; p=0.029).ConclusionsNon-gonadal hypopituitarism is common in prolactinomas, especially larger tumors. Tumor size was the strongest predictor of both the presence and recovery of hormonal deficits, with an optimal cut-off of 17 mm. Long-term follow-up is essential, as many patients, especially those with smaller tumors, recover pituitary function after treatment, with gonadal and adrenal axes showing the highest likelihood.